EFEKTIVITAS KEPEMIMPINAN KEPALA DESA KINALI KECAMATAN SIAU BARAT UTARA KABUPATEN SITARO - MANGARO, STYVEN OCTAVIO; POSUMAH, JOHNNY; TAMPI, GUSTAAF BUDDY (JURNAL ADMINISTRASI PUBLIK, 2020)
Attitude and behavior in carrying out the duties as the village head shows a personality that is able to directand provide good wisdom for the community. It was then found that the ability of the village head in termsof understanding the duties and functions and responsibilities supported by the background of strata 1education in the field of law, competency in accordance with the responsibility of giving a large role for thevillage head in understanding the duties and functions held. Unpartiparative leadership is also an obstaclein the effectiveness of the village chief's leadership. In the study, it was found that people do not understandthe various government activities and development programs carried out by the government.Keywords : effectiveness of leadership